Racking Analysis Instrument Mastery Test Concepts in Learning Science Using the RADEC Model in Elementary School Students - Muthi'ah, Nur Maya; Sukmawati, Wati (Jurnal Penelitian Pendidikan IPA, 2023)
The study's objective was to assess the content's validity, reliability, and degree of difficulty for third-grade students in one of the East Jakarta elementary schools utilizing the RADEC learning model by analyzing the pre-test and post-test items using the Rasch Racking model of analysis. The results of the Radec learning model showed that students with low and high abilities experienced a change in the concept of student effectiveness for the better. This research is a quantitative study, namely the evaluation of learning outcomes using descriptive quantitative methods with data collection techniques using pre-test and post-test questions. In early 2023, The learning activity was conducted using data from 32 student respondents. The result indicated the validity of the suitability level of the item, with ten questions found to be valid. The difficulty level of the questions, in general, is in the medium category, meaning that they are excellent because they are relatively straightforward. The conclusion is that the analysis of the items using the Rasch model in the learning evaluation activities through the pre-test and post-test is valid with excellent categories of 50% and good 50%. The question's difficulty level is excellent